Immunotherapy and brain metastasis in lung cancer: connecting bench side science to the clinic - Rios-Hoyo, Alejandro; Arriola, Edurne (Frontiers in Immunology, 2023)
Brain metastases (BM) are the most common form of intracranial malignant neoplasms in adults, with a profound impact on quality of life and traditionally associated with a dismal prognosis. Lung cancer accounts for around 40-50% of BM across different tumors. The process leading to BM is complex, and includes local invasion, intravasation, tumor cells circulation into the bloodstream, disruption of the blood-brain barrier, extravasation of tumor cells into the brain parenchyma and interaction with cells of the brain microenvironment, among others. Once the tumor cells have seeded in the brain parenchyma, they encounter different glial cells of the brain, as well as immune cells. The interaction between these cells and tumor cells is complex and is associated with both antitumoral and protumoral effects. To overcome the lethal prognosis associated with BM different treatment strategies have been developed, such as immunotherapy with immune checkpoint inhibitors, particularly inhibitors of the PD-1/PD-L1 axis, which have demonstrated to be an effective treatment in both non-small cell lung cancer and small cell lung cancer. These antibodies have shown to be effective in the treatment of BM, alone or in combination with chemotherapy or radiotherapy. However, many unsolved questions remain to be answered, such as the sequencing of immunotherapy and radiotherapy, the optimal management in symptomatic brain metastases, the role of the addition of anti-CTLA-4 antibodies, etc. The complexity in the management of BMs in the era of immunotherapy requires a multidisciplinary approach to adequately treat this devastating event. The aim of this review is to summarize evidence regarding epidemiology of BM, its pathophysiology, current approach to treatment strategies, as well as future perspectives.